Penyelesaian Sengketa Hak Dan Kewajiban Suami Istri Pasca Perceraian Di Pengadilan Agama Pariaman Kelas IB - Miasiratni Miasiratni; Mahliyanti Adelia Warman; Doni Eka Putra (Universitas Sumatera Barat, 2026)
The resolution of disputes over the rights and obligations of husband and wife after divorce falls under the jurisdiction of the Religious Court, aiming to provide legal certainty and justice for the parties. This study aims to examine the process of resolving disputes regarding the rights and obligations of husband and wife after divorce at the Pariaman Class I.B Religious Court and the obstacles encountered in its implementation. The research method used was descriptive empirical legal research. Data were obtained through interviews and literature review, then analyzed qualitatively. The results indicate that dispute resolution is carried out through the trial process in accordance with applicable procedural law, with a focus on mediation. Obstacles encountered include low legal awareness among the parties and non-compliance with the implementation of court decisions. Therefore, efforts are needed to improve legal understanding and optimize the implementation of decisions to ensure the fulfillment of the rights and obligations of the parties after divorce.